UAIG (Urban Areas of Illegal Genesis) (re) living to (re) integrate - Graça, A; Paio, A. (CA²RE CONFERENCE FOR ARTISTIC AND ARCHITECTURAL (DOCTORAL) RESEARCH, 2018)
The ongoing research intends to develop a strategy for the (re) qualification of the public space in the UAIG (Urban Areas of Illegal Genesis), through the introduction of an intervention methodology – collaborative participatory processes. The strategies of intervention in the public space have launched new challenges to research in architecture. In a demanding society with strong participatory and collaborative citizenship, public space increasingly assumes an important role in urban practices. The lack of public space in areas of illegal genesis in Metropolitan Area of Lisbon (MLA), shaped the PhD research question: How public space make UAIG´s (re) living to (re) integrate it in Lisbon Metropolitan Area dynamics? Participation means the collaboration of people pursuing objectives that they themselves have defined. A public space is one which, in its design and in its use, stimulates a sense of belonging to a wider community beyond the bounds of the strictly private sphere. It is, then, a scenario that fosters contract between difference people mixing uses and meeting place for individual and collective interests. The answer is to adopt methods and instruments that allow the creation of a methodology for the analysis of a great transversality of scales – territory, neighbourhoods and public space. This research aims to contribute to a generic model of good practices applicable to any process of requalification of the urban space of the UAIG.